(3fXe OYe GdbQGQGJ dEOGQI GdYedjGJ hHMhK GdYedjGJ (B/s - (3dWaj, aGgjOs; e; (3SQhQ, SQhQ Ydj EHQGgjes; (3GdYHO GdefYe, YHO GdefYe Hf EHQGgjes; (3YHO GdQMef, eMeO jMjis; (3dWaj, aGgjO(B.s ((3GdQjGV (B:s (3OGQ GdeQjN ddfTQ,s, 2007)
(3gPG GdcJGH Yf fXe OYe GdbQGQGJ GdEOGQI GdYedjGJ, hHMhK GdYedjGJ, jJOGhd GSJNOGe GdMGSH GdBdj aj Md GdcKjQ ef eTGcd EOGQI GdYedjGJ HGSJNOGe CSGdjH HMhK GdYedjGJ ddhUhd Edi GdbQGQGJ GdNGUI HMd gPg GdeTGcd(B. (3hbO Hdfj GdcJGH Ydi fXe HQGeL GdMGSH GdeSLdI Ydi GdbQU GdeQf GdeQab Hg(B. (3hgj fXe HQGeL UOjbI ddeSJNOe , hJJejR HJWGHb JYdjeGJ GdJTZjd dcd HQfGeL ef GdHQGeL GdHGdZ YOOgG hGMO hYTQhf HQfGeLG jJfGhd cd efgG CMO ehVhYGJ EOGQI GdYedjGJ hHMhK GdYedjGJ(B. (3hjhUi HGSJNOGe GdcJGH cfhY ef Odjd GdeYed aj OQGSI ebQQGJ EOGQI GdYedjGJ, hHMhK GdYedjGJ dJOQjH GdOGQS Ydi GSJNOGe GdMGSH GdBdj aj Md eKd gPg GdeTGcd GdCeQ GdPj CUHMaj ZGjI GdCgejI aj JOQjS eKd gPg GdebQQGJ dcd ef GdOGQSjf aj cdjGJ GdJYdje GdEOGQj, hcdjGJ GdgfOSI hcdjGJ GdWHjI Ch GdYdhe GdPjf jOQShG HMhK YedjGJ, Ch EOGQI YedjGJ jHOC GdcJGH HJYQja GSJNOGe fXe GdHQGeL, hcjajI JTjjOgG Ydi GdbQU hcjajI HOg fXe GdHQGeL HUaI YGeI(B. (3haj hGMO hYTQjf aUdG jJfGhd cd efgG cjajJI GSJNOGe fXje GdHQGeL aj CMO JWHjbGJ EOGQI GdYedjGJ, hHMhK GdYedjGJ(B. (3hGdJWHjbGJ gj (B: (3JMdjd GdbQGQ HGdLOGhd, hJMdjd GdbQGQ HGdCTLGQ, hbHd GdSdGed GdRefjI hGdGfMOGQ GdeJYOO hJMdjd GdehbY, hJMdjd GdJNWjW GdOGNdj, hehGRfI GdNW, hGdHQeLI GdNWjI, hGdHQeLI ZjQ GdcSQjI GdYGeI, hWQjbI GdJNUjU, hWQjb Gdfbd, hfeGPL JOab GdTHcGJ Ydi GdJhGdj(B.s
Keywords: (3GJNGP GdbQGQGJs; (3HMhK GdYedjGJs